2017
DOI: 10.1186/s41199-016-0020-y
|View full text |Cite
|
Sign up to set email alerts
|

Radiotherapy plus EGFR inhibitors: synergistic modalities

Abstract: Locally advanced (stage III or IV) squamous cell carcinoma of the head and neck (SCCHN) often requires multimodal treatment, consisting of a combination of surgery, radiation, and/or systemic therapy, namely chemotherapy or targeted agents. The expression of the epidermal growth factor receptor (EGFR) has been detected in more than 90% of all cases of SCCHN and has been correlated with decreased survival rates, resistance to radiotherapy, loco-regional treatment failure, and increased rates of distant metastas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 69 publications
(67 reference statements)
0
9
0
Order By: Relevance
“…Nonetheless, there is a rather general consensus on the correlation between EGFR expression levels, poor prognosis and worse treatment outcomes in patients with HNSCC, while there is no definitive evidence that EGFR gene copy number and mutations may have prognostic value in this group of cancers ( 1 , 2 , 8 , 17 , 33 ). In particular, EGFR overexpression has been associated with radiotherapy resistance, loco-regional treatment failure, higher rates of metastatization, and with reduced disease-free, progression-free and overall survival in different cohorts of patients ( 8 , 17 , 77 , 78 ). Worthy of note, several authors remarked that the significance of the observed correlations is critically dependent on the assessment of EGFR protein levels in cancer tissues by means of quantitative image analysis and scoring systems, taking into account both intensity and extent of the immunostaining ( 17 , 78 ).…”
Section: Erbb Receptors and Prognosis Of Hnsccmentioning
confidence: 99%
“…Nonetheless, there is a rather general consensus on the correlation between EGFR expression levels, poor prognosis and worse treatment outcomes in patients with HNSCC, while there is no definitive evidence that EGFR gene copy number and mutations may have prognostic value in this group of cancers ( 1 , 2 , 8 , 17 , 33 ). In particular, EGFR overexpression has been associated with radiotherapy resistance, loco-regional treatment failure, higher rates of metastatization, and with reduced disease-free, progression-free and overall survival in different cohorts of patients ( 8 , 17 , 77 , 78 ). Worthy of note, several authors remarked that the significance of the observed correlations is critically dependent on the assessment of EGFR protein levels in cancer tissues by means of quantitative image analysis and scoring systems, taking into account both intensity and extent of the immunostaining ( 17 , 78 ).…”
Section: Erbb Receptors and Prognosis Of Hnsccmentioning
confidence: 99%
“…For many HNSCCs, the response to a single-agent chemotherapy or monoclonal antibody alone remains dismally low mandating a multi-modal approach combining surgery, chemotherapy and/or radiation [ 46 , 47 ]. Early in vitro studies demonstrated that high concentrations of EGF slowed tumor growth, presumably through negative feedback and resulted in radiosensitization of human HNSCC cells [ 48 , 49 ].…”
Section: Egfr Alterations and Radiation Responsementioning
confidence: 99%
“…The predictive value of EGFR has been very well established using various methodologies such as immunohistochemical analysis of tumor samples, fluorescent in situ hybridization, tissue microarray, and gene sequencing [ 69 , 70 , 71 ]. Multiple studies have shown that the overexpression of EGFR in HNSCC directly correlates with worse outcomes [ 47 , 54 , 72 , 73 , 74 ]. Meta-analyses have shown that EGFR overexpression is associated with reduced overall survival (OS), and progression-free survival (PFS), and disease-free survival (DFS) with the magnitude of these effects varying from study to study [ 75 , 76 , 77 , 78 ].…”
Section: Egfr Alterations As Prognostic Indicators For Disease and Th...mentioning
confidence: 99%
“…8 Epidermal growth factor receptortargeted therapies for HNSCC Epidermal growth factor receptor (EGFR) is a prototypical receptor tyrosine kinase that is overexpressed in HNSCC and affects the proliferation, apoptosis, angiogenesis, and metastasis of tumor cells (Nair et al, 2022). Many studies have shown that the overexpression of EGFR in HNSCC directly correlates with worse outcomes (Temam et al, 2007;Agulnik, 2012;Bossi and Platini, 2017). To date, EGFR blockades are attractive targets in HNSCC patients and anti-EGFR strategies such as IgG-based monoclonal antibodies (mAbs), have shown acceptable clinical benefits.…”
Section: Adoptive T Cell Therapymentioning
confidence: 99%